Effect of heat treatments on 316 stainless steel parts fabricated by wire and arc additive manufacturing: Microstructure and synchrotron X-ray diffraction analysis - Rodrigues, Tiago A.; Escobar, J. D.; Shen, Jiajia; Duarte, Valdemar R.; Ribamar, G. G. [UNESP]; Avila, Julian A. [UNESP]; Maawad, Emad; Schell, Norbert; Santos, Telmo G.; Oliveira, J. P. (Elsevier, 2021)
Different geometrical features and intricate parts can now be fabricated by wire and arc additive manufacturing (WAAM). Even though a broad range of applications rises with this technology, the processed metallic materials still follow metallurgy rules. Therefore, undesired phases may appear during the multiple thermal cycles affecting the fabricated part. One of the most used stainless steel in the industry is the 316 L, which provides a combination of high corrosion resistance and mechanical properties. In this study, 316 L stainless steel walls were fabricated by WAAM and submitted to several heat treatments to understand the precipitation kinetics of secondary phases and observe the δ-ferrite dissolution with synchrotron X-ray diffraction measurements. The as-built samples presented δ-ferrite dendrites in an austenite (γ) matrix. In-situ observations showed σ precipitation during the first minutes of isothermal holding at 950 °C, from direct precipitation on the δ-ferrite islands. Solubilization heat treatments at 1050 and 1200 °C resulted in an undissolved amount of ferrite of approximately 6.5% and 0.4%, respectively. The amount of δ-ferrite showed a direct relationship with the hardness values. This work combined advanced materials characterization and thermodynamic calculations to rationalize the microstructure evolution upon the use of heat treatments in WAAM-fabricated 316 L stainless steel parts.
Keywords: In-situ phase transformation, high energy synchrotron x-ray diffraction; Sigma phase; Stainless steel; Wire and arc additive manufacturing